Hybrid historical simulation VaR and ES : performance in developed and emerging markets - Sasa Zikovic; Randall Filer (Center for Economic Studies and ifo Institute (CESifo), 2009)
We introduce a new hybrid approach to joint estimation of Value at Risk (VaR) and Expected Shortfall (ES) for high quantiles of return distributions. We investigate the relative performance of VaR and ES models using daily returns for sixteen stock market indices (eight from developed and eight from emerging markets) prior to and during the 2008 financial crisis. In addition to widely used VaR and ES models, we also study the behavior of conditional and unconditional extreme value (EV) models to generate 99 percent confidence level estimates as well as developing a new loss function that relates tail losses to ES forecasts. Backtesting results show that only our proposed new hybrid and Extreme Value (EV)-based VaR models provide adequate protection in both developed and emerging markets, but that the hybrid approach does this at a significantly lower cost in capital reserves. In ES estimation the hybrid model yields the smallest error statistics surpassing even the EV models, especially in the developed markets.
Keywords: G24; C14; C22; C52; C53; 330; value at risk; expected shortfall; hybrid historical simulation; extreme value theory; bootstrapping; Value at Risk; Kapitalertrag; Extremwertanalyse; Bootstrap-Verfahren; Schätztheorie; Theorie; Aktienindex; Schätzung; Welt